Pincang laku kepimpinan pengetua menurut perspektif guru: satu kajian kes - Abdul Ghani Abdullah,; Abd. Rahman Hj. Abd Aziz,; Tang, Keow Ngang (penerbit ukm, 2008)
The aim of this study is to provide knowledge constructively and comprehensively of teacher perspectives of principals’ leadership misbehavior (mistreatment) and its destructive effects emotionally and physically on teachers. Symbolic interaction approach was used to study 10 teachers who believed they were subjected to short and long term mistreatment from their school principal. The results briefly discuss the perception of principals’ leadership misbehavior from the perspective of teachers and its effects on teachers’ performance in classroom. Implication of the study for future administrators and further research is discussed.